Analisis Keterampilan Proses Sains Peserta Didik Kelas VIII Dalam Pembelajaran Daring Di SMP - Pramudiyanti Pramudiyanti; Reni Munazir (Universitas Lampung, 2021)
This study aims to obtain information about the level of science process skills skills of class VIII students during online learning on motion system material. The sample in this study was 161 class VIII students at SMP Muhammadiyah 3 Bandar Lampung for the 2020/2021 academic year. The research design used was Cross Sectional Ex Post Facto using Saturated Sampling technique. Methods of data collection using the method of tests, interviews, and questionnaires. Based on the results of research, the ability of science process skills carried out in online learning at SMP Muhammadiyah 3 Bandar Lampung belongs to the category